GENDER TRAINING IN PAKISTAN: AN ANALYSIS FOR WAY FORWARD - Anita Anis Allana; Kausar S. Khan; Sohail Bawani (European Scientific Journal, ESJ, 2015)
The decade of 1970s focused on women and development, with 1974 declared as Women’s Year by the UN, followed by the decade for women (1975 – 1985). The First World Conference on women (Mexico 1975) drew attention to the need for bringing women into the development sector; by 1985 global discourse recorded a shift from women in development (WID) to gender and development (GAD). In Pakistan the notion of gender entered the development discourse by mid 1980s, and a proliferation of gender training took place. By 1995, when the Fourth World Conference on women took place in Beijing, gender training was well established in Pakistan, and a loose network of gender trainers was also established. . As gender trainings took place in different NGOs, a sense of having hit a plateau began to be felt by some gender trainers. There was no evidence available to gauge the impact of gender training or ascertain whether new depths are being explored. Furthermore, gender training appeared to have become de-politicized. This paper shares the findings of a scoping review undertaken to understand the scope (focus, depth and nature) of literature on gender trainings in Pakistan, and to highlight the gaps in training. The paper also discusses the efforts of an informal network of gender trainers that tried to extend the agenda of gender trainings and how these need to be incorporated in the gender agenda for a more holistic approach. A way forward is also identified in the paper.